(untitled) (American Journal of Pedagogical and Educational Research, 2025)
This article analyzes the impact of long-term smartphone use (especially in cases of excessive daily screen time) on the cognitive functions—attention, memory, reading skills—and socio-psychological aspects of children aged 7–10 years. The research methodology includes a review of literature, surveys, and analysis of previous scientific studies. The results show that prolonged daily screen exposure may lead to decreased attention, memory problems, and weakened social interactions among children. The conclusion and recommendations propose limiting children’s screen time, encouraging balanced activities, and strengthening parental and school-based monitoring of screen use.